Factor improving entrepreneurial opportunity recognition for graduate entrepreneur - Abu Bakar, Muhamad Shahbani; Hassan, Syahida; Ta'a, Azman; Yasin, Azman; Suhaimi, Safiah; Zainal Adnan, Ahmad Amri (Advanced Scientific Research, 2020)
Pioneering opportunity acknowledgment assumes a significant job in perceiving and form an open door into an endeavor characterizes a business visionary. Research additionally shows that accomplished business visionaries quest and sweep for data to find openings. In light of other research, there is less spotlight on inquire about on finding experimentally demonstrated systems and strategies to create and upgrade opportunity acknowledgment in understudy business visionaries. This study aims to explore factors that improving entrepreneurial opportunity recognition. The study found three factors are family background, individual desire, and education which measures the elements that improving entrepreneurial opportunity recognition. The factor will be evaluated through quantitative methods enable student entrepreneurs to generate more business ideas that are more innovative and viable. This component article introduces the discoveries of the investigation, and examines potential consequences and remedies.